Structural changes in cattle immature oocytes subjected to slow freezing and vitrification. - Haron, Abdul Wahid; Thein, Myint; El-Hafez, Enas A.; Abas, M. O.; Mohd Azam, K.; Othman, Fauziah; Yusoff, Rosnina; Hajarian, Hadi (University of Agriculture, Faisalabad, 2012)

(untitled)
This study was conducted to evaluate the effect of different cryopreservation methods (slow-freezing and vitrification) on structural changes of bovine immature oocytes. Bovine ovaries were collected from local abattoirs. Cumulus-oocytecomplexes (COCs) were retrieved using aspiration method from 2-6 mm follicles. In Experiment 1, selected oocytes were randomly divided into 4 treatment groups namely freezing solution-exposed, frozen-thawed, vitrification solution-exposed and vitrified-thawed and then oocytes abnormalities were examined under a stereomicroscope. In Experiment 2, oocytes were randomly allocated to the same grouping as experiment 1 plus control group. Following freezing or vitrification, all oocytes were fixed in glutaraldehyde and processed for transmission electron microscopy. In experiment 1, there was a higher incidence of abnormalities in the frozen-thawed and vitrified-warmed oocytes compared to those in freezing solution and vitrification solution-exposed groups (P <0.05). In experiment 2, there were marked alterations in the perivitelline space, microvilli and vesicles of frozenthawed and vitrified-warmed oocytescharacterized by loss of elasticity and integrity of cytoplasmic processes and microvilli following cooling and warming. In conclusion, ethylene glycol-based freezingand vitrification solutions are suitable choices for cryopreservation of immature oocytes and most organelles are able to retain their normal morphology followingcryopreservation and thawing processes